Water Shortage at Several Sub Watershed into Wonogiri DAM - Murtiono, Ugro Hari; Wuryanta, Agus (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2019)
The study was conducted at several selected sub-watersheds (Temon, Wuryantoro, Alang, and Keduang Sub-watersheds) in Wonogiri District. These four sub-watersheds are main rivers whose outlets flow into Wonogiri Dam. The study calculated the water supply and water demand for various uses at four sub-watersheds. The Thornwaite and Mather method was used to estimate the water supply. The results indicated that: (1) The water supply of Temon Sub-watershed was 35,435,875 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â and the annual water demand was 51,053,247 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â, therefore there was a deficit of 30,59 % per year; (2)Ã‚Â  The water supply of Wuryantoro Sub-watershed was 17,788,417 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â and the water demand was 22,413,430 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â per year, therefore the deficit was 20.64% per year; (3) The water supply of Alang Sub-watershedÃ‚Â  was 31,372,317 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â per year and the water demand was 69,566,500 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â per year, therefore the deficit was 54.90% per year; (4) The water supply of Keduang Sub-watershed was 438,527,889 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â and the water demand was 452,611,219 m3Ã‚ÂÃ‚ÂÃ‚ÂÃ‚ÂÃ‚Â per year, thus, the deficit was 3.11%Ã‚Â  per year; (5) those sub-watersheds need improvements especially effective water resources plans, water allocation and distribution based on the determined priority, e.g., retention basin, low evapotranspiration re-vegetation, well-managed infiltration, water resources protection, and water reservoir construction.